Bridging the gaps: Challenges and Opportunities - Vidal, Alain (CGIAR Consortium, 2014)
Bridging the gaps between AR and ARD Challenges and Opportunities- presented by Alain Vidal, Senior Advisor, Capacity Development and Partnerships, CGIAR Consortium at the AKIS-ARCH Workshop, Brussels, 26-27 May 2014